THE EFFECT OF ACCOUNTABILITY AND TRANSPARENCY ON CAMPAIGN FUND COMPLIANCE WITH INTERNAL CONTROL AS A MODERATING - Zakiah Fitri Salsabila Yulzam; Hardi Hardi; Meilda Wiguna (Jurnal Al-Iqtishad, 2025)
This study analyses the impact of accountability and transparency on campaign finance reporting compliance, with the internal control system as a moderating variable, in Political Parties participating in Pekanbaru City Election. Using a quantitative approach with 102 respondents and PLS-based SEM analysis, the findings reveal that accountability and transparency significantly affect compliance. However, the internal control system does not moderate the effect of accountability and weakens the influence of transparency. The study underscores the need to strengthen internal control systems, enhance public trust, and improve regulatory frameworks and supervision to uphold democratic integrity.